Hubungan Tingkat Pengetahuan Dengan Stigma Masyarakat Pada Penderita Tuberkulosis Paru Di Wilayah Kerja Puskesmas Demak 1 - Niken Averenka; Moch. Aspihan; Iskim Luthfa; Nutrisia Nu’im Haiya (STIKes Ibnu Sina Ajibarang, 2025)
Stigma is a negative label given by a person or group to others. In this study, stigma is shown to people with pulmonary tuberculosis which can be influenced by one of the factors, namely community knowledge. Lack of public knowledge about the prevention and transmission of pulmonary tuberculosis will give rise to a negative stigma against the disease and people with pulmonary tuberculosis so that it can interfere with social life, the role of family and society. In addition, the stigma given by the community is able to interfere with the rights of pulmonary tuberculosis sufferers to get treatment, carry out social activities, and meet economic needs. This study aims to find out the relationship between the level of public knowledge and stigma towards pulmonary tuberculosis patients. The research method used is quantitative research with a Cross sectional design. Sampling used the Slovin formula with a total of 100 respondents and the sampling technique used Incidental sampling with the criteria for inclusion of respondents residing in the working area of the Demak 1 health center and aged 20-49 years. Knowledge level as an independent variable and stigma as a dependent variable, this study uses a knowledge level and stigma questionnaire processed using the Spearman test with the independent variable being the level of knowledge and the dependent variable being stigma. The results of the spearman test from 100 respondents obtained a significancy result of 0.000 (p <0.05) and a correlation value of -0.368 which shows that there is a relationship, with a fairly close strength and a negative relationship direction. In this study, there was a relationship between the level of knowledge and community stigma in patients with pulmonary tuberculosis in the working area of the Demak 1 Health Center with a strong relationship that was negative.